KEMAMPUAN HIGHER ORDER THINKING SKILL (HOTS) DALAM PEMBELAJARAN BERDIFERENSIASI SD 19 PALEMBANG - Florens Dianni Nurhabiba; Misdalina Misdalina; Tanzimah (STKIP Subang, 2023)
This study aims to describe the ability of higher order thinking skills in differentiated learning at SD Negeri 19 Palembang. Method research used is descriptive quantitative research method with pre-experimental form and one-group pretest-posttest design. The population in this study amounted to 54 students consisting of class IV A who totaling 25 students, IV B totaling 29 students. In this research using 1 class for sampling using purposive sampling, namely class IV A. Data collection techniques used were tests, questionnaire and documentation. The data analysis technique used is the n - gain test. The results of the pretest and posttest n-gain ability higher order thinking skills is 0.55 medium category. HOTS ability in differentiated learning applied is as expected, meaning that the average student can parse information in HOTS questions and determine the initial steps to find correct answer. Keywords: Ability, Higher Order Thinking Skill, Learning Differentiate